Potential fecundity of an introduced population, Keban Dam Lake, Elazig, Turkey, of freshwater crayfish, Astacus leptodactylus leptodactylus (Esch., 1852) - Harlioglu, MM; Barim, Ö; Türkgülü, I; Harlioglu, AG (Elsevier, 2004)
Potential fecundity of an introduced population, Keban Dam Lake, Elazig, Turkey, of freshwater crayfish, Astacus leptodactylus leptodactylus (Esch., 1852), was investigated in the present study. The results showed that there was not a linear relationship between female size and pleopodal egg number. The results also showed that although there is an increase in the mean pleopodal egg number with an increase in size (carapace length, CL), it is not the most important factor affecting potential fecundity in A. leptodactylus (slope= 1.9294). Mean pleopodal egg number was 305.93 (S.E.=8.82) for the size range of 47-76 mm CL (N=96). The maximum pleopodal egg number was 588 for the crayfish in a 72-mm CL. The present study showed that Keban Dam Lake population of A. leptodactylus has more potential fecundity than the other populations in Turkey. The egg-bearing capacity of female A. leptodactylus caught from Keban Dam Lake could improve efficiency in controlled hatchery production of juveniles. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Astacus leptodactylus; crayfish; fecundity; pleopodal egg number